2003
DOI: 10.1002/ajmg.a.20477
|View full text |Cite
|
Sign up to set email alerts
|

Constipation, polyps, or cancer? let PTEN predict your future

Abstract: The inherited hamartoma polyposis syndromes encompass several distinct clinical syndromes with different genetic bases, Cowden syndrome (CS), Bannayan-Riley-Ruvalcaba syndrome (BRRS), juvenile polyposis syndrome (JPS), and Peutz-Jeghers syndrome (PJS). Germline mutations in PTEN, encoding a tumor suppressor phosphatase on 10q23.3, is associated with 80% of CS and 60% of BRRS. JPS is caused by mutations in MADH4 and BMPR1A, encoding two members of the TGFB superfamily. Germline mutations in LKB1 (STK11) are ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 73 publications
(125 reference statements)
0
24
0
Order By: Relevance
“…Thus, for all practical purposes, diagnostic congruence was 100% . Several authors have reported patients who were said to have ''Proteus syndrome'' with PTEN mutations Smith et al, 2002] and others have repeatedly stated that PTEN mutations are a cause of a subset of patients with ''Proteus syndrome'' Eng, 2003;Kirk et al, 2004].…”
Section: Misdiagnosismentioning
confidence: 99%
“…Thus, for all practical purposes, diagnostic congruence was 100% . Several authors have reported patients who were said to have ''Proteus syndrome'' with PTEN mutations Smith et al, 2002] and others have repeatedly stated that PTEN mutations are a cause of a subset of patients with ''Proteus syndrome'' Eng, 2003;Kirk et al, 2004].…”
Section: Misdiagnosismentioning
confidence: 99%
“…Pten heterozygous mice (Pten +/À ) develop a spectrum of neoplasias in organs, such as the breast, thyroid, endometrium, and prostate, which closely resembles the situation in humans with PTEN mutation (5,(8)(9)(10). Somatic PTEN mutations in humans occur with a wide distribution of frequencies in sporadic primary tumors, with the highest frequencies in endometrial carcinomas and glioblastoma (11). PTEN mutation is among the most common genetic alterations reported in human prostate cancers, with loss of heterozygosity (LOH) of PTEN found in 30% of primary prostate cancers (12)(13)(14) and 63% of metastatic prostate cancer tissue samples (6).…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal polyposis [2][3][4][5][6][7][8][9][10][11][12] Glycogenic acanthosis [2,8,11,13] Intestinal hyperplasia 14…”
Section: Gastrointestinal Feature Referencesmentioning
confidence: 99%
“…Loss of function of PTEN contributes to tumourigenesis-specifically, hamartoma formation [1]. Multiple systems are involved and patients often demonstrate a wide spectrum of manifestations and presentations, including complications of gastrointestinal hamartomas, mucocutaneous abnormalities and an increased cancer risk [2]. There remains limited literature on cases reported in Asia.…”
Section: Introductionmentioning
confidence: 99%